2013
DOI: 10.1105/tpc.113.113167
|View full text |Cite
|
Sign up to set email alerts
|

p-Hydroxybenzoyl-Glucose Is a Zwitter Donor for the Biosynthesis of 7-Polyacylated Anthocyanin in Delphinium

Abstract: ORCID IDs: 0000-0002-3002-368X (Y.O.); 0000-0001-7474-9493 (N.S.).The blue color of delphinium (Delphinium grandiflorum) flowers is produced by two 7-polyacylated anthocyanins, violdelphin and cyanodelphin. Violdelphin is derived from the chromophore delphinidin that has been modified at the 7-position by Glc and p-hydroxybenzoic acid (pHBA) molecules. Modification of violdelphin by linear conjugation of Glc and pHBA molecules to a Glc moiety at the 7-position produces cyanodelphin. We recently showed that ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
(67 reference statements)
1
45
0
Order By: Relevance
“…The retention time of the new peak was consistent with that of authentic delphinidin 3-O-rutinoside-7-O-glucoside (Dp3R7G) ( Figure 1E) prepared as described previously (Nishizaki et al 2013). This analysis confirmed that glucosylation at the 7 position of anthocyanin was catalyzed by an acyl-glucose dependent glucosyltransferase in C. medium.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…The retention time of the new peak was consistent with that of authentic delphinidin 3-O-rutinoside-7-O-glucoside (Dp3R7G) ( Figure 1E) prepared as described previously (Nishizaki et al 2013). This analysis confirmed that glucosylation at the 7 position of anthocyanin was catalyzed by an acyl-glucose dependent glucosyltransferase in C. medium.…”
supporting
confidence: 49%
“…Thus, transcription of CmAA7GT was greatest just before flower opening. This pattern of expression has also been found for other AAGTs that are expressed specifically in flower tissues (Matsuba et al 2010;Miyahara et al 2012;Nishizaki et al 2013).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Differences in modification of the major anthocyanin caused differences in maximum absorption, and gave rise to the orange, red and pale pink coloration groups. Although there were clear phenotypic differences between the 'CRD' (red flowers) and 'SKH' and 'SHP' (pale pink flowers) varieties, the anthocyanin structures in the three varieties were similar; in particular, the 7-position of Pg was modified with the same residues that are believed to play an important role in determining flower color (Nishizaki et al 2013). The HPLC analysis and ESI-MS analysis suggested that the structure of the main anthocyanin had less effect on color quality in varieties with red, orange and pale pink flowers.…”
mentioning
confidence: 99%
“…This result implies that both acylations are carried out during gentiodelphin biosynthesis by the same enzyme, which was accordingly renamed as anthocyanin 5,3′-aromatic acyltransferase (A5/3′AT). Recently, vacuolar-type glucosyltransferases (GTs) and ATs, which utilize acyl-glucose as the glucosyl and acyl donors, respectively, have been identified to be involved in anthocyanin modification steps in several species, including Arabidopsis, carnation, agapanthus, and delphinium (Matsuba et al 2010;Miyahara et al 2013;Miyahara et al 2012;Nishizaki et al 2013). These GTs and ATs belong to a completely distinct protein family of cytosolic UGTs and acyl-CoA dependent ATs.…”
Section: The Flavonoid Biosynthetic Pathway In Japanese Gentian Flowersmentioning
confidence: 99%